2018
DOI: 10.21475/ajcs.18.12.07.pne1035
|View full text |Cite
|
Sign up to set email alerts
|

Initial growth of Brazilian Firetree (Schizolobium parahyba (Vell.) S.F.Blake) fertilized with phosphorus in Red-Yellow Latosol

Abstract: Due to the scarcity of information on the use of fertilizers on the Brazilian Firetree (locally known as guapuruvu), this study aimed to evaluate the initial stages of guapuruvu (Schizolobium parahyba (Vell.) S.F.Blake.) plant growth using different doses of phosphorus (P). The experiment was conducted within a greenhouse environment in dystrophic Red-Yellow Latosol soil samples from the Brazilian Cerrado as the substrate in plastic containers with a capacity of 10 dm 3. The experimental design was completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…In turn, plants grown at the maximum P dose (200 mg dm -3 ) showed a 24% reduction in relation to the maximum SDM production (Figure 3A). These results corroborate Araújo et al (2018), who reported that high P doses may reduce SDM production, and therefore it is essential to ensure the adequate availability of this nutrient.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In turn, plants grown at the maximum P dose (200 mg dm -3 ) showed a 24% reduction in relation to the maximum SDM production (Figure 3A). These results corroborate Araújo et al (2018), who reported that high P doses may reduce SDM production, and therefore it is essential to ensure the adequate availability of this nutrient.…”
supporting
confidence: 90%
“…In guapuruvu plants (Schizolobium parahyba (Vell.) S.F.Blake), Araújo et al (2018) also observed that leaf P concentrations 6/8 were positively influenced by increasing P doses, showing increasing linear behavior as a function of applied doses.…”
Section: /8mentioning
confidence: 83%